Wild thing : the short, spellbinding life of Jimi Hendrix - Norman, Philip, 1943- (Liveright Publishing Corporation, 2020)
"Commemorating the fiftieth anniversary of Jimi Hendrix's death, the best-selling author of Shout! delivers a compelling new biography of the legendary guitarist. Celebrated as the most innovative guitarist ever to play, Jimi Hendrix (1942-1970) is renowned for symphonic solos and virtuosic picking (sometimes, with his teeth). But, as Philip Norman describes, before Hendrix was setting guitars aflame onstage, he was a shy kid in Seattle, plucking at a broken ukulele and looking out for his father, who chided him for playing left- handed. Interweaving new interviews with friends, lovers, bandmates, and his family, Wild Thing vividly reconstructs Hendrix's remarkable life- from playing in segregated clubs on the Chitlin' Circuit to earning stardom in Swinging London in 1966. For more than four mind- boggling years Hendrix found unparalleled success, making historic appearances at Monterey and Woodstock while becoming the highest paid musician of his day, but it all abruptly ended with his tragic death in the sordid basement of a London hotel. Filled with insights into the greatest moments in rock history, Wild Thing reveals the endlessly complex figure behind the unforgettable riffs"--